Two cases of severe COVID-19 in gestational week 27 and 28 respectively, after which both pregnancies proceeded to term. (November 2021) - Östling, H.; Ugarph-Edfeldt, M.; Hildén, K.
Highlights: Two pregnant women with severe COVID-19 successfully treated, delivered at term. Multidisciplinary management is essential in severe COVID-19 in pregnancy. The risks of acute surgery in critically ill patients should be considered. Abstract: COVID-19 in pregnancy increases the risk of caesarean section. We present two cases of late gestation pregnant women with severe COVID-19. Both were successfully treated with mechanical ventilation without termination of pregnancy and, following recovery from COVID-19, had vaginal deliveries at term. These two cases demonstrate the possibility of treating pregnant women with severe COVID-19 with mechanical ventilation in the late second and early third trimesters without them having a pre-term delivery. With a multidisciplinary approach, such management could avoid the maternal risks of surgery during a severe infection and, at the same time, enable term birth with a lower risk of neonatal complications.